Transcriptome-Wide Characterization of Alkaloids and Chlorophyll Biosynthesis in Lotus Plumule - Sun, Heng; Song, Heyun; Deng, Xianbao; Liu, Juan; Yang, Dong; Zhang, Minghua; Wang, Yuxin; Xin, Jia; Chen, Lin; Liu, Yanling; Yang, Mei (Frontiers in Plant Science, 2022)
Lotus plumule is a green tissue in the middle of seeds that predominantly accumulates bisbenzylisoquinoline alkaloids (bis-BIAs) and chlorophyll (Chl). However, the biosynthetic mechanisms of these two metabolites remain largely unknown in lotus. This study used physiological and RNA sequencing (RNA-Seq) approaches to characterize the development and molecular mechanisms of bis-BIAs and Chl biosynthesis in lotus plumule. Physiological analysis revealed that exponential plumule growth occurred between 9 and 15 days after pollination (DAP), which coincided with the onset of bis-BIAs biosynthesis and its subsequent rapid accumulation. Transcriptome analysis of lotus plumule identified a total of 8,725 differentially expressed genes (DEGs), representing 27.7% of all transcripts in the lotus genome. Sixteen structural DEGs, potentially associated with bis-BIAs biosynthesis, were identified. Of these, 12 encoded O-methyltransferases (OMTs) are likely involved in the methylation and bis-BIAs diversity in lotus. In addition, functionally divergent paralogous and redundant homologous gene members of the BIAs biosynthesis pathway, as well as transcription factors co-expressed with bis-BIAs and Chl biosynthesis genes, were identified. Twenty-two genes encoding 16 conserved enzymes of the Chl biosynthesis pathway were identified, with the majority being significantly upregulated by Chl biosynthesis. Photosynthesis and Chl biosynthesis pathways were simultaneously activated during lotus plumule development. Moreover, our results showed that light-driven Pchlide reduction is essential for Chl biosynthesis in the lotus plumule. These results will be useful for enhancing our understanding of alkaloids and Chl biosynthesis in plants.